After Jokowi’s First Term – The Papuan Riots : Flash in the Pan? - Mariska, Made Ayu (2019)
While Jakarta is busy with the plan to move the capital to East Kalimantan, riots have broken out throughout Papua over two weeks. Is it an isolated incident, or is it a part of a larger problem?